Is There a Limit? A Risk Assessment Model of Liposuction and Lipoaspirate Volume on Complications in Abdominoplasty. Issue 4 (April 2018) - Vieira, Brittany L.; Chow, Ian; Sinno, Sammy; Dorfman, Robert G.; Hanwright, Philip; Gutowski, Karol A.
Abstract : Background: Combining liposuction and abdominoplasty is controversial because of concerns for increased complications and potential for vascular compromise of the abdominoplasty flap. Also, the lipoaspirate volume in abdominoplasty is regulated in some areas to as little as 500 ml when performed with abdominoplasty. This study measures abdominoplasty complication rates when performed with and without trunk liposuction, and evaluates the effect of lipoaspirate volume on complications. Methods: Abdominoplasty and liposuction of the trunk procedures were identified in the Tracking Operations and Outcomes for Plastic Surgeons database. Multivariate regression models determined the effect of liposuction with abdominoplasty on complications compared with abdominoplasty alone and determined the effect of liposuction volume on complications. Results: Eleven thousand one hundred ninety-one patients were identified: 9638 (86.1 percent) having abdominoplasty with truncal liposuction and 1553 (13.9 percent) having abdominoplasty alone. Overall complication rates were 10.5 percent and 13.0 percent, respectively. Combined liposuction and abdominoplasty was independently associated with a reduced risk of both overall complications ( p = 0.046) and seroma ( p = 0.030). Given existing laws limiting liposuction volume to 500 or 1000 ml in combination with abdominoplasty, each of these thresholds was evaluated, with no effect on complications. Surprisingly, increasing liposuction volume was not independently associated with an increased risk of any complication. Conclusions: When done by board-certified plastic surgeons, abdominoplasty with truncal liposuction is safe, with fewer complications than abdominoplasty alone. Regulations governing liposuction volumes in abdominoplasty are arbitrary and do not reflect valid thresholds for increased complications. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Supplemental Digital Content is available in the text.